2015
DOI: 10.2147/ijn.s86053
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive therapeutic solid lipid nanoparticles for reducing P-glycoprotein-mediated drug efflux of multidrug resistant cancer cells

Abstract: In this study, a novel pH-responsive cholesterol-PEG adduct-coated solid lipid nanoparticles (C-PEG-SLNs) carrying doxorubicin (DOX) capable of overcoming multidrug resistance (MDR) breast cancer cells is presented. The DOX-loaded SLNs have a mean hydrodynamic diameter of ~100 nm and a low polydispersity index (under 0.20) with a high drug-loading efficiency ranging from 80.8% to 90.6%. The in vitro drug release profiles show that the DOX-loaded SLNs exhibit a pH-controlled drug release behavior with the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Through this strategy, DOX forms an ion pair with a lipophilic anion, improving its lipophilicity and the affinity for the lipid matrix. This strategy is well described in the literature and has been used in several studies that utilized different counter ions to improve the DOX lipophilicity and its affinity for different lipid-based systems [33,41,[43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In the present study, OA was used as the counter ion.…”
Section: Discussionmentioning
confidence: 99%
“…Through this strategy, DOX forms an ion pair with a lipophilic anion, improving its lipophilicity and the affinity for the lipid matrix. This strategy is well described in the literature and has been used in several studies that utilized different counter ions to improve the DOX lipophilicity and its affinity for different lipid-based systems [33,41,[43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In the present study, OA was used as the counter ion.…”
Section: Discussionmentioning
confidence: 99%
“…A fast release profile of doxorubicin was observed at pH 4.7 as compared to pH 7.4. The enhanced rate of drug release at low pH may be due to the decreased electrostatic attractions among the negatively charged lipid core and the positively charged doxorubicin (Chen et al, 2015 ; Mishra et al, 2018 ).…”
Section: Drug Encapsulation/incorporation and Release From Slns And Nlcsmentioning
confidence: 99%
“…Curcumin has very low bioavailability and high metabolism. Curcumin-loaded NLCs have shown 6.4 times higher plasma concentration and improved brain targeting (Chen et al, 2015 ). Lim et al reported 2-fold increase in brain concentration of itraconazole from the synthesized NLCs (Lim et al, 2014 ).…”
Section: Applications Of Slns and Nlcs In Drug Delivery Systemsmentioning
confidence: 99%
“…The ever-growing number of studies confirmed that this strategy might lead to the development of new class of drug delivery systems [ 97 ]. To date, a number of stimulus factors, including light, radiofrequency (RF) energy, magnetic field, enzymes or alternation in pH value, have been explored [ 9 , 31 , 98 101 ]. Recently, Yingyuad et al described new PEGylated siRNA-nanoparticles activated by human leukocyte elastase (HLE) or matrix metalloproteinase-2 (MMP-2), both present in the extracellular spaces of tumor in order to promote invasion and metastasis of cancerous cells via degradation of basement membrane and extracellular matrix barrier.…”
Section: Triggered Drug Delivery By Stimuli-sensitive Nanoparticlesmentioning
confidence: 99%
“…Such were designed for treatment of DOX-resistant breast cancers. Importantly, the solubility of DOX increased in acidic environment, which improves the release rate of drug [ 31 ]. Moreover, mild acidic conditions, characteristic for tumor environment facilitate release of DOX from polymer-conjugated MSNs due to hydrolysis of the acid-sensitive acetal linkage and dissociation of polymer coating layer, protecting payload drug from release in physiological pH [ 108 ].…”
Section: Triggered Drug Delivery By Stimuli-sensitive Nanoparticlesmentioning
confidence: 99%